Bedside pediatrics - Mustafa, Sultan; Waheed, Sumbal (A.M. Graphics, 2014)
The book covers all matters related to bedside pediatrics. These includes the art of history taking, developmental screening, general and systematic examination, neontala examination, short cases examination, ECG outlines and x-ray chest, vaccinations: EPI and non-EPI, pediatric procedures, pediatric formulas, common pediatric definitions, normal laboratory findings, illustrations, pictures and tables.